Pengembangan Instrumen Tes Kemampuan Membaca Bermuatan AKM untuk Murid Sekolah Dasar - Effendi, M. Syahrun; Murti, Sri; Aisah, Vella Sabrila; Hidayat, Riski Yongki (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The development of reading ability test instruments for elementary school students is crucial in efforts to strengthen students' reading literacy skills to be used as a foundation for successful lifelong learning as, emphasized in the Merdeka Belajar policy. This study aims to determine the procedure for developing reading ability test instruments containing AKM for elementary school students. The implementation of the study used the R&D (research and development) development model with the ADDIE (analyze, design, develop, implementation, evaluation) development model at Elementary School 2 Lubukngin, Selangit District, Musi Rawas Regency. Data collection was carried out using questionnaires, documentation, and tests. The analysis was carried out in the following stages; development needs analysis stage; design preparation stage including formulating reading ability test objectives, compiling grids based on cognitive aspects of literacy that have been determined by the Ministry of Education and Culture, compiling instructions for working on questions and determining the type or form of questions in the assessment instrument based on 25 questions; Next, the development stage is the validation of the test instrument from two validators with Aikens'V and the score obtained from validator I is 0.66 and validator II is 0.716. The score from the two validators is proof that the score is in the fairly valid category; at the implementation stage it is proven that the results of student responses to the AKM-based reading ability test instrument are 79.78% and are included in the practical category; and the final evaluation proves that this test instrument is suitable for widespread use. This study concludes that the AKM-based reading ability test instrument developed is quite valid. The student's score from the product trial using this AKM-based reading ability test instrument overall is in the lower category, namely 44.75. Therefore, it can be stated that the AKM-based reading ability test instrument can measure students' reading ability effectively and can be implemented by teachers practically.